2020
DOI: 10.1186/s12906-020-02887-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adeABC efllux pump encoding genes and antimicrobial effect of Mentha longifolia and Menthol on MICs of imipenem and ciprofloxacin in clinical isolates of Acinetobacter baumannii

Abstract: Background: Acinetobacter baumannii is an opportunistic pathogen that causes nosocomial infections especially in patients in intensive care units (ICUs). Accordingly, the aim of our study was to detection of adeABC efllux pump encoding genes and antimicrobial effect of the essential oil of Mentha longifolia and Menthol on the minimum inhibitory concentration (MIC) of imipenem and ciprofloxacin in clinical isolates of A. baumannii. Methods: A total of 75 clinical isolates of A. baumannii were collected. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
2
10
1
Order By: Relevance
“…Similar findings were reported in Iraq where the AdeABC efflux pump system was 96% prevalent in clinical isolates of A. baumannii [61]. Mahmoudi et al [62] also mentioned that AdeABC efflux pump system genes were present in more than 90% of A. baumannii clinical isolates in their study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar findings were reported in Iraq where the AdeABC efflux pump system was 96% prevalent in clinical isolates of A. baumannii [61]. Mahmoudi et al [62] also mentioned that AdeABC efflux pump system genes were present in more than 90% of A. baumannii clinical isolates in their study.…”
Section: Discussionsupporting
confidence: 85%
“…baumannii [ 61 ]. Mahmoudi et al [ 62 ] also mentioned that AdeABC efflux pump system genes were present in more than 90% of A . baumannii clinical isolates in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Other bacterial species were identified, including commensal bacteria. Phylogenetic analysis and maximum-likelihood indicated that A. baumannii 01, 07, 09, 12,27,28,44,45,51,53, 60, 61, and 64 strains were genetically related 99.99% of similarity (correlated with the phenotypic resistance assays). ESKAPE bacteria distribution (including other genera) in medical devices, inert surfaces, medical personnel, and patients from the ICU are shown in Figure 1.…”
Section: Genetic Identification Of Eskape Bacteriamentioning
confidence: 98%
“…Several successful combinations of FQs with natural products against MDR A. baumannii were previously reported [62,63]. However, few studies were conducted on the use of some non-selective beta-blockers such as PR in combination with antimicrobial agents [7] or carvedilol alone [14].…”
Section: Plos Onementioning
confidence: 99%